Between Flexibility and Language Exposure: Translanguaging and Language Immersion Perceptions in University English Classrooms - Yulie Asni; Hasmi Hasmi; Rezkiani Nur Amalia (Indonesian TESOL Journal, 2026)
In multilingual English classrooms, the use of translanguaging has grown into a pedagogical issue, particularly in balancing comprehension of learners and target language exposure. This study aims to explore lecturers’ and students’ perceptions of translanguaging and language immersion as pedagogical tools in the English language learning process. A qualitative case study design was employed. Data were collected through classroom observations and semi-structured interviews with lecturers and undergraduate students in the English Education Department of IAIN Parepare, Indonesia, and analyzed thematically. The findings show that both lecturers and students perceive translanguaging and language immersion as complementary instructional practices. Translanguaging was viewed as facilitating comprehension, promoting classroom inclusion, and reducing learners’ anxiety by lowering the affective filter, as proposed in Krashen’s theory, by allowing the use of Bahasa Indonesia and local languages. In contrast, language immersion was perceived as enhancing students’ fluency, confidence, and authentic use of English through sustained exposure and communicative practice. However, participants emphasized that immersion is most effective when implemented flexibly and supported by translanguaging, particularly for learners with diverse proficiency levels. The study highlights the importance of integrating flexibility and language exposure to support English language learning in multilingual higher education contexts.